First record of Cecilioides acicula (Müller, 1774) (Mollusca: Ferussaciidae), from Buenos Aires Province, Argentina - Díaz, Ana Carolina (2017)
Ceálioides acicula (Müller, 1774), family Ferussaciidae, is native to the Palaearctic region but has been dispersed around the word by human activity. Here, we report the presence of this introduced species in La Plata city, Buenos Aires province, Argentina. This snail is largely subterranean and frequently is found in old graves in association with skeletal remains. Our samples were collected from sediments from the Municipal Cemetery of La Plata, Buenos Aires province, Argentina.